Preserving Malacca Cultural Heritage Sites through Cendol Cup Packaging Design - Muhammad Faizul Bin Azhar; Norfadilah Kamaruddin; Fathin Nur 'Izzah Mohd Taslim; Mohd Hashim Johari (Research in Management of Technology and Business, 2026)
Malacca, a UNESCO World Heritage Site, is rich in cultural heritage, but modernization threatens its visibility. This study explores integrating Malacca’s building heritage into cendol cup packaging to enhance cultural appreciation. Cendol, a popular dessert in Baba Nyonya culture in Malacca, serves as an ideal medium to bridge tradition with daily life. Aligning with Sustainable Development Goal 11 (SDG 11), the research examines how Malacca’s heritage buildings can inspire packaging design and assesses consumer perceptions. A mixed-methods approach is applied, combining qualitative analysis of heritage elements and expert insights with quantitative consumer feedback through surveys. The study hypothesizes that heritage-themed packaging enhances cultural engagement. By embedding cultural elements into everyday products, this research offers an innovative strategy for heritage preservation, fostering public awareness and appreciation while ensuring Malaysia’s cultural legacy remains relevant for future generations.